Upaya Meningkatkan Kinerja Pegawai Kantor Perpustakaan Dan Arsip Daerah Kabupaten Banyumas - Kriswibowo, Arimurti; Harsanto, Bambang Tri; Kurniasih, Denok (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2017)
Human resource management becomes a challenge in the process of organizing the public organization. The successful of human resources management can be impactful on the achievement of public organizations goals. Bad administration  of human resources can have further influence on the performance of the organization. Espesially in Banyumas, 8 job departements still have low achievements, below 90% of RKPD targets. Two of them are in SKPD of Library Office and Regional Archive of Banyumas Regency This research aims to determine the performance of the Public Library and Archive Office and find several factors that can improve performance in public organizations. This research was conducted in the Banyumas Public Library and Archive Office, and the respondents of all office employees. This research use deductive model and using data analysis method of correlation kendall tau and ordinal regression The results showed that the performance of employees at the Public Library and Archive Office is good but not optimal. This study also found the relationship and influence where the work discipline affect the performance of 20.3%, while the employee's ability to affect the performance of 24.4%, and employee perceptions of the work environment affect the performance of 32.2%. Keyword: Human Resources, Employees Performance, Library Management, Disipline, Ability, Work Environment DOI https://doi.org/10.33005/jdg.v7i2.1205